2010
DOI: 10.3109/07420528.2010.510227
|View full text |Cite
|
Sign up to set email alerts
|

PHOTIC INDUCTION OF Fos IN THE SUPRACHIASMATIC NUCLEUS OF AFRICAN MOLE-RATS: RESPONSES TO INCREASING IRRADIANCE

Abstract: African mole-rats (family Bathyergidae) are strictly subterranean rodent species that are rarely exposed to environmental light. Morphological and physiological adaptations to the underground environment include a severely reduced eye size and regressed visual system. Responses of the circadian system to light, however, appear to be intact, since mole-rats are able to entrain their circadian activity rhythms to the light-dark cycle and light induces Fos expression in the suprachiasmatic nucleus (SCN). Social o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…Moreover, the epiphysis has not been found in H. glaber ([113], single-animal study, confirmed by V. Manskikh in our group). H. glaber does not respond significantly to the increased Fos gene expression level in the suprachiasmatic nucleus of the hypothalamus in response to increased illumination, which is different from the response of other visually impaired fossorial species, such as the common mole rat Cryptomys hottentotus [114,115].…”
Section: Naked Mole Rat Neotenycontrasting
confidence: 66%
“…Moreover, the epiphysis has not been found in H. glaber ([113], single-animal study, confirmed by V. Manskikh in our group). H. glaber does not respond significantly to the increased Fos gene expression level in the suprachiasmatic nucleus of the hypothalamus in response to increased illumination, which is different from the response of other visually impaired fossorial species, such as the common mole rat Cryptomys hottentotus [114,115].…”
Section: Naked Mole Rat Neotenycontrasting
confidence: 66%
“…However, the mole-rat circadian system remains intact, and compares anatomically in size to the circadian structures in the brains of other rodents [1012]. Light also reaches the circadian clock in the SCN, as illustrated by expression of Fos protein in response to light stimulation [13,14]. Furthermore, many mole-rat species can entrain their locomotor activity patterns to light cycles and also display endogenous rhythms of locomotor activity in the absence of light cues [1518].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that changes in light intensity of the photophase did not affect locomotor activity, urine production or urinary 6-SMT in the same manner in M. namaquensis and R. pumilio (Van der Merwe et al, 2017). These variations could stem from differences in the SCN response to light of different intensities and wavelengths (Bonmati-Carrion et al, 2017;Dkhissi-Benyahya et al, 2000;Oosthuizen et al, 2010), and most likely reflected adaptations to the vastly distinct photo-environments of the temporal niches to which these two species are confined in their natural habitats.…”
Section: Discussionmentioning
confidence: 73%